STIMULATION OF SOCIAL EMOTIONAL DEVELOPMENT IN EARLY CHILDHOOD EDUCATION - La Jeti; Ode Yahyu Herliyani Yusuf (International Journal of Education, Information Technology, and Others, 2018)
This study aims to describe the stimulation of social emotional development which includes: children's social emotional abilities, how to stimulate social emotional development and how the role of the teacher group B Setia Kindergarten of Baubau. This research uses descriptive method with a qualitative approach. The subjects of the research is the head master and teachers. The setting of the research in Setia Kindergarten of Baubau. The method of Data collection uses observation, interview, documentation. Besed on the data analyse finding of the research show: 1) social emotional abilities, namely children can get along, socialize and communicate with friends and teachers well, cooperate, be patient waiting for their turn, care and help friends who have difficulty doing assignments in class, sharing food and toys, succumbing to friends , happy to play with friends, not easily angry, love each other and enjoy playing together otherwise there are some children who have not been able to work together, waiting for their turn, easily angry, and difficult to play together. 3) method of stimulating social emotional development that is through habituation, developing children's self-confidence, exemplary and playing. This method can stimulate children's social and emotional development optimally. Teachers have a very important role in child development by involving themselves as role models, mentors, facilitators and motivators for children.